Clinical experience with everolimus in the second-line treatment of advanced renal cell carcinoma. (October 2015) - Alesini, Daniele; Mosillo, Claudia; Naso, Giuseppe; Cortesi, Enrico; Iacovelli, Roberto
Everolimus is an oral inhibitor of mammalian target of rapamycin (mTOR-I) and is currently approved for the treatment of metastatic renal cell carcinoma (mRCC) after failure of first-line vascular endothelial growth factor receptor tyrosine kinase inhibitor (TKI). In this narrative review, we aim to report the available evidence about the use of everolimus as second-line therapy for mRCC. A literature search was performed using PubMed/MEDLINE and abstracts from major conferences on clinical oncology as sources. We report data from prospective as well as retrospective and real world data studies and we analyze the safety and efficacy profile of everolimus as second-line therapy for mRCC. Although different drugs are currently available for the second-line treatment of mRCC, everolimus represents a feasible and safe option in this setting, especially for patients who have experienced high-grade toxicity or are still carrying TKI-related toxicities from first-line treatment.